QUANTITATIVE AND QUALITATIVE ANALYSIS OF TRADITIONAL CHEESE PRODUCTION IN ROMANIA - Daniela POPA; Ioana TOMA; Maria Cristina STERIE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Certification of traditional products is a voluntary quality scheme, recognized in the EU, which provides producers with viable tools to identify and promote products. The national regulation was issued in compliance with the provisions of Government Decision no. 1,016/2004 on measures for the organization and implementation of information exchange in the field of technical standards and regulations, as well as the rules on information society services between Romania and the Member States of the European Union, as well as the European Commission, as subsequently amended and supplemented. Among the conditions for attesting traditional food products is the production capacity of one or more products. The indicator on the maximum quantity of certified product/products regulated by the specific normative act allows and encourages the agricultural activities of small producers in rural areas, which have an important role in the rural economy and, in particular, in disadvantaged areas. The sustainable development of products belonging to this niche will ensure the sustainability of traditional production and the maintenance of local traditions. The traceability of agri-food products, by applying and developing the concept of "short agri-food chain" will provide consumers with fresh food from local production, at affordable prices. Easy information of consumers interested in these products is possible due to the creation and posting on the Ministry of Agriculture and Rural Development- MARD website of the National Register of Traditional Products. Through this paper, an analysis of traditional products in the category of dairy products and cheeses has been made, so as to identify the potential and promote its use for areas in Romania by registering such products, using in this sense the statistical basis of information of the National Institute of Statistics, NIS, in terms of livestock.